OPTICAL SPECTRA OF L - DWARFS - Pavlenko, Ya. (Одеські астрономічні публікації, 2017)
Theoretical spectra, of L-dwarfs (Teff <2200 K) were computed for a. grid of the "dusty" C-model atmospheres of Tsuji (1998). To fit the observed spectra of L-dwarfs we used two additional (evristic) suggestions: molecular densities of TiO and VO governed the visible spectra, of M-dwarfs are reduced due to the extra depletion of V and Ti atoms into grains in atmospheres of Teff <2200 K; There are (a few) additional opacity k sources in L-dwarf atmospheres; A few kinds of k = f(A) dependences were used to get "the better fit" of observed spectra of L-dwarfs, We show: We may fit the observed sequence of L-dwarf spectra using in the frame of our simple model; Observed sequence of the L-dwarf spectra is the temperature sequence; At first time, the region of 860 nm contained CrH bands is well fitted; There are a few possibilities to get the reliable fits to the observed spectra; In the frame of our approach we have found the solution even for the case of G1229B.